THE ISLAMIC CONCEPT OF FEMINISM IN SIGER LAMPUNG - Bahrudin Yusuf Zen (Pascasarjana IAIN Metro, 2021)
Lampung is a province located in the South end of Sumatra island. People will find a glamorous and big icon in yellow color called Siger when they enter the gate of this province. Siger is the symbol of honor for people in Lampung. Unfortunately, there are various kinds of violence suffered by women in this province. Those violence practices include harsh treatment, rape, and common law which verily not beneficial for women. Based on this phenomenon, this research tries to depict the real meaning of Siger as the symbol of honor for Lampung society as well as its relevance toward Islamic concept. After being analyzed using a Library Research approach, it can be concluded that Sigercarries the deep values of feminism and it indicates the concept of gender equality. Those feminism values, then, reflected in society life so the feminine characteristics which full of care, respect, tender and polite become more preferred in daily living. However, the concept carried in Siger also has the relevance toward Islamic concept that reveals the same case.